Development of indices tutorial package for lower secondary school students / Mazatulaniza Zainal - Zainal, Mazatulaniza (2006)
Nowadays, multimedia is used in various areas such as advertisement, entertainment and education. The advancement of multimedia technology has reform current education system for its capability to enhance learning rate in the learning activity. Mathematics is a scientific discipline students experience as both a source of knowledge and a challenge for acquiring mathematical skills. Unfortunately, mathematics classes are often concerned purely with memorizing information and learning skills. Thus, this paper will discuss about the implementation of multimedia in developing a tutorial package. The tutorial package will introduced Indices to low secondary school students within age of 13 to 15 years old. The objective of this project is to develop multimedia learning package for teaching and learning Indices that could be used as Computer-Based Training (CBT) tools. In the package, the concept of Indices is applied and elaborated. The package will include learning modules with quizzes. This project had been developed using authoring tools which is Macromedia Director MX. Product of combination multimedia elements such as graphics, sound, text, animation and video in one digital environment could create an interesting and interactive learning environment.